Contrast enhanced computed tomography in the characterization of acute pancreatitis and related complications - Swetha Anupindi; Syed Younus Uz Zaman; Nagendra R. Patil (Al Ameen Medical College, 2024)
Background: Contrast Enhanced CT (CE-CT) is considered to be the gold standard imaging modality in the evaluation of patients with acute pancreatitis. The role of imaging is not only to diagnose acute pancreatitis but also to demonstrate the presence and extent of pancreatic necrosis and complications of acute pancreatitis. Method: The present cross-sectional study was performed in the Department of Radio-Diagnosis, Basaveshwara Teaching and General Hospital, Kalaburagi on patients referred from the Department of General Medicine and Department of General Surgery from March 2022 to August 2022.Based on the inclusion and exclusion criteria, a total of 20 patients were included in the study after obtaining informed written consent by the patients. A plain CT abdomen scan followed by triple-phased Contrast-Enhanced CT of the abdomen after oral and IV contrast administration. Result: Males comprised 85% and females 15% of the study and males exceeded the number of female patients in all the age groups. In the present study, the most common etiology was found to be alcoholism (60%), cholelithiasis (25%), and other idiopathic causes (15%). 40% (8/20) of patients with acute pancreatitis had vascular complications. 25% of patients with vascular complications had Splenic Vein Thrombosis. 32% and 28% of patients with acute pancreatitis had Ascites and Pleural Effusion respectively. Acute pancreatitis is associated with a wide variety of complications. Conclusion: Contrast Enhanced Computed Tomography helps in the accurate detection of vascular and non-vascular complications of acute pancreatitis and guides the management decision and reduces morbidity. Timely diagnosis and management will be useful to lower morbidity and mortality.